Diagnostic accuracy of iridocorneal angle assessment using anterior segment optical coherence tomography and gonioscopy in glaucoma patients - Neha Adlakha; Eva Rani Tirkey; Sonu Badole; Sujata Lakhtakia; Charudatt Chalisgaokar (The Pan-American Journal of Ophthalmology)
Purpose: The study aimed to compare the assessment of anterior chamber angle (ACA) by gonioscopy and anterior segment optical coherence tomography (AS-OCT) in detecting angle closure in glaucoma patients. Materials and Methods: The study group included 1000 eyes of 500 glaucoma patients. A comprehensive ophthalmological examination, including best-corrected visual acuity, AS slit-lamp assessment, applanation tonometry, static and dynamic gonioscopy, and AS-OCT, was performed. ACA in a quadrant was categorized as closed if posterior trabecular meshwork could not be observed on gonioscopy, and on AS-OCT, closed ACA was defined by the presence of any contact between the iris and wall of angle anterior to the scleral spur. Statistical analyses were performed with SPSS software. Continuous variables were described as mean and variation of each observation from the mean value. Results: The mean ± standard deviation (SD) of intraocular pressure was 18.9 ± 8.29 mm. The male-and-female ratio was 0.98:1. Thirty percent of the superior angles, 16% of the inferior angles, 17% of the nasal angles, and 17% of the temporal angles were classified as closed by gonioscopy and open on AS-OCT. Conclusion: AS spectral-domain OCT (SD-OCT) appears to be equally sensitive in assessing the angle of anterior chamber in Indian eyes as gonioscopy. Because gonioscopy is a subjective technique, it is limited by interobserver variation, whereas SD-OCT allows for a more objective assessment of the ACA with enough resolution to allow for qualitative and quantitative ACA assessment.